FIELD PERFORMANCE FAMILY PLANNING OFFICER - Dicky Yusuf; Rajindra Rajindra; Haris Abd Kadir; Marwana Marwana; Mutmainnah Mutmainnah (Jurnal Sinar Manajemen, 2018)
One effort to realize a quality family is through family planning program (KB). The purpose of this study to determine the factors that affect the performance of Field Officers KB in implementing KB extension tasks. The research used is descriptive research which is used to give deep picture about the empirical condition in the field. This study determines the object of Performance of Field Officer of KB, PPKBD and SUB PPKBD. Data collection was done through questionnaires distributed to representative respondents. The respondents of this research are EUS Community, Religion Leader, Village Apparatus in Research Area. The population of this study is the EFA community in Donggala District spread throughout the District within Donggala District. Determination of the size of the sample based on the characteristics of the District, then obtained a sample of District by 10 Districts. Each of the sub-districts was drawn by 30 minimal samples from the EFA community, village officials and religious leaders of each sample. The results showed that factors affecting the performance of family planning instructors in carrying out extension work were good. Factors that affect the performance of PPKBD in carrying out extension KB tasks are also quite good. Factors affecting the performance of SUB PPKBD in carrying out extension KB tasks are also included good category.